Analisis Motivasi Kerja Dalam Upaya Meningkatkan Produktivitas Kerja Karyawan Pada Rumah Makan Jatinangor, Sumedang - Amiruliya Regina Yustiffa; Rhayina Dwi Anandita; Rakhmat Haryono (STIE Bangkinang Publishing, 2023)
The purpose of this study is to analyze work motivation in an effort to increase employee work productivity. The research method used in this research is descriptive qualitative research method. The results of the study indicate that there is a relationship between work motivation and employee work productivity. Where motivated employees will increase the effectiveness and efficiency of their work, which also increases the level of work productivity. Work motivation comes from external and internal sources. Internal arises from the need for employees to meet their needs. At the same time, external comes from the certainty of wages, bonuses, work environment, management attitudes and workplace regulations.